2023
DOI: 10.1002/pits.23050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of teachers' intrinsic motivation on students' intrinsic motivation: The mediating role of teachers' motivating style and teacher‐student relationships

Abstract: Teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning are important contributors to effective teaching and learning, and exploring their relationships and influencing mechanisms can clarify the path to promote teachers' professional development and students' overall growth. In our study, 44 secondary school teachers and 2461 secondary school students completed questionnaires, and a multilevel structural equation model was used to explore the influence of teachers' intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Further mediating-effects tests showed that teachers' internal motivation to teach mediated the effects of their readiness to teach and the teacher-child relationship, but the mediating effect of teachers' external motivation to teach was not of considerable significance. This study confirmed that teachers' internal motivation to teach highly predicted the quality of the teacher-child relationship, which also supports previous research [32,55]. According to the self-determination theory, the internal motivation of teachers to teach is one of the most autonomous forms of motivation [56], so that teachers engage in the teaching profession with the aim of deriving pleasure and satisfaction from the educational activity itself.…”
Section: Mediating Role Of Teachers' Motivation To Teach and Self-eff...supporting
confidence: 88%
See 1 more Smart Citation
“…Further mediating-effects tests showed that teachers' internal motivation to teach mediated the effects of their readiness to teach and the teacher-child relationship, but the mediating effect of teachers' external motivation to teach was not of considerable significance. This study confirmed that teachers' internal motivation to teach highly predicted the quality of the teacher-child relationship, which also supports previous research [32,55]. According to the self-determination theory, the internal motivation of teachers to teach is one of the most autonomous forms of motivation [56], so that teachers engage in the teaching profession with the aim of deriving pleasure and satisfaction from the educational activity itself.…”
Section: Mediating Role Of Teachers' Motivation To Teach and Self-eff...supporting
confidence: 88%
“…MT not only affects their own professional goals, teaching behaviors, and job satisfaction, but also significantly impacts students' motivation and learning [31]. As Zou et al (2023) found in their research, teachers' motivation to teach shapes the ways in which teachers motivate their students, which, in turn, affect the quality of the teacher-student relationship [32]. Drawing from these findings, we believe that there is a close correlation between teachers' motivation to teach and the teacher-child relationship.…”
Section: Motivation To Teach (Mt) As a Mediatormentioning
confidence: 99%
“…Pedagogical and psychological theories suggest that the relationship between teachers' intrinsic motivation for teaching and students' intrinsic motivation for learning is complex, with various internal mechanisms at play (Ahn et al, 2021). Teachers' motivation can not only directly influence students' motivation but also enhance their intrinsic motivation by fostering teaching practices that support autonomy, competence, and relatedness, fulfilling students' basic psychological needs (Kalyar et al, 2018;Zou et al, 2023). In essence, motivated teachers can serve as role models, inspiring students to engage more deeply in their studies and arousing enthusiasm, especially in areas like technology.…”
Section: Teacher Variables: the Role Of The Teachermentioning
confidence: 99%